APLIKASI BEBERAPA INOKULAN Rhizobium DAN INTERVAL PEMOTONGAN HIJAUAN PAKAN TERNAK Stylosanthes guyanensus TERHADAP KANDUNGAN NITROGEN TANAH DI LAHAN KERING - Kusriningrum Rochiman (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 1995)
This research on discovering compatible Rhizobium inoculum for Stylosanthes guyanensis, the influence of defoliation interval on forage and the influence of interaction between inoculum and defoliation interval on nitrogen content in dry land had been conducted in Ranuklindungan Village, Grati, Pasuruan since July 1993 until November 1994. This experiment used factorial with randomized block design, with two factor (Rhizobium inoculum : without inoculum, inoculum of Stylosanthes guyanensis planted soil, legin of Leguminosae Cover Crops (Calopogonium mucunoides), Legin of Glycine max ; and defoliation interval ; without interval defoliation, 40 days defoliation interval, 60 days defoliation interval, and three replications. The inoculation which was manifested on nodule formation influences the nitrogen content in soil on 12 month old. Stylosanthes guyanensis with the best result on inoculation of Stylosanthes guyanensis planted soil. The defoliation interval doesn't influence the nitrogen content in soil. There are no interaction between inoculum and defoliation interval on nitrogen content in soil. The 4-8 month-old Stylosanthes guyanensis need supplementary nitrogen of soil media, the 8-12 month-old ones can increase nitrogen content of soil media up to 17.39 % by inoculation of Stylosanthes guyanensis planted soil and up to 12.58 % by 60 days defoliation interval.